Tell me - Jackson, Lisa. (New York : Kensington Books, 2013)
Twenty years ago, Blondell O'Henry was convicted of murdering her eldest daughter and wounding her two other children. The prosecution said that beautiful, selfish Blondell wanted to be rid of them to be with her lover. Now Blondell's son, Niall, has recanted his testimony and demolished the case. Reporter Nikki Gillette is determined to get the true story, and not just for professional reasons. Blondell's murdered daughter, Amity, was Nikki's childhood friend.
Keywords: Journalists -- Fiction; Murder -- Fiction; Savannah (Ga.) -- Fiction